Bank Management and Control Strategy, Capital and Risk Management - Wernz, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Strategic planning, including the required quantitative methods, is an essential part of bank management and control. In this book capital, risk and yield are treated comprehensively and seamlessly. And a thorough introduction to the advanced methods of risk management for all sectors of banking is discussed. In addition, directly applicable concepts and data such as macroeconomic scenarios for strategic planning and stress testing as well as detailed scenarios for operational risk and advanced concepts for credit risk are presented in straightforward language. The book analyzes the effects of macroeconomic and regulatory developments such as the set of Basel III rules on planning, and it also presents and discusses the consequences for actively meeting these challenges, especially in terms of capital. A wealth of essential background information from practice, international observations and comparisons, along with numerous illustrative examples, make this book a useful resource for established and future professionals in bank management, risk/return management, controlling and accounting.
1 Outline -- 2 Bank Management and Steering -- 3 Banks in their Regulatory and Economic Environment -- 4 Risk Modeling and Capital - Credit Risk (Loans) -- 5 Risk Modeling and Capital - Counterparty Credit Risk (EPE) -- 6 Risk Modeling and Capital - Credit Risk (Securitizations) -- 7 Risk Modeling and Capital - Market Risk -- 8 Risk Modeling and Capital - Operational Risk -- 9 Risk Modeling - Asset Liability Management (ALM) -- 10 Appendix: A-IRB Formulas for the Derivation of Risk-Weighted Assets -- 11 Appendix: Credit Portfolio Modeling -- 12 Appendix: Country Risk/Issuer Risk -- 13 Appendix: Settlement Risk ans Systemic Risk -- 14 Appendix: Historical Data.
Keywords: Economics; Finance; Economics -- Statistics; Macroeconomics; Economics/Management Science; Finance/Investment/Banking.; Quantitative Finance; Statistics for Business/Economics/Mathematical Finance/Insurance.; Financial Economics; Macroeconomics/Monetary Economics